Moisture: Protein Ratio in broiler chicken breasts affected with muscle defects (Research, Society and Development, 2022)
The genetic evolution of broiler strains triggered gains in performance indexes and body changes. That said, there is a challenge for the poultry industries to comply with the legal standards of the Moisture:Protein Ratio (MPR) contents to stop fraud by inserting water into the meat. In this sense, it is known that muscle defects such as wooden breast and white striping influence the centesimal composition of the meat, identifying cuts with higher moisture and lower protein functionality. Another important factor in the MPR variation is the weight of the poultry, given that the smaller the carcass, the greater its absorption of water in the slaughter process. Therefore, the aim of this research was to evaluate the MPR and its association with the occurrence and severity of muscle defects, as well as the influence of broiler breast weight on these variables. A total of 240 samples of 42-day-old broiler breasts were collected, weighed, classified by their muscle defects severity, and evaluated for their centesimal composition of moisture and protein through means of near-infrared reflectance spectroscopy (NIRS). It was verified in the results that the mean of the MPR presented a significant difference (p